Effects of different training strategies with a weight vest on countermovement vertical jump and change-of-direction ability in male volleyball athletes - Freitas-Junior, C. G.; Fortes, L. S.; Santos, T. M.; Batista, G. R.; Gantois, P.; Paes, P. P. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: Weight vest training (WVT) is a strategy used to improve the physical performance of athletes. The objective of this study was to determine the effects of different training strategies with weight vests on vertical jump and change-of-direction ability (CODA) in male volleyball athletes. METHODS: Fifteen volleyball athletes (22.87±3.04 years, 83.22±10.84 kg, 1.86±0.69 m) participated in a six-week training programme and were randomized into three groups: weight vest plyometric training (WPG), weight vest technical-tactical training (WTG) and a control group (CG). The additional weight of 7.5% of individual body mass was employed in the experimental groups. Before and after the WVT, athletes performed countermovement vertical jump (CMJ) and CODA (t-test) tests. RESULTS: Two-way ANOVA with repeated measures showed that CMJ height increased in all training groups (P<0.05), with the WTG inducing greater CMJ height gains in comparison to the CG (P<0.05). According to magnitude-based inference, the effects of the WTG strategy were "very likely" beneficial for the CMJ compared to the CG. In addition, t-test time decreased similarly among the three training groups (P<0.05). CONCLUSIONS: The results suggested that WVT may be incorporated in a volleyball training routine as an effective strategy for improving the CMJ performance in male volleyball athletes.